The Use of Computers and Smartphones Associated with Decreased Visual Acuity in Mataram Informatics Engineering Students - Ni Made Sumartyawati; Kartini Ulfianti; I Made Eka Santosa; Antoni Eka Fajar Maulana; Sukardin Sukardin; Nurul Ilmi (UIMA Press, 2023)
Background: Excessive use of computers and smartphones can cause complaints of dizziness and watery eyes. if it happens continuously, it will be harmful to eye health. Objectives: The study aimed to examine the relationship between the use of computers and smartphones with a decrease in visual acuity. Methods: The study was correlational with a cross-sectional design involving 65 students and selected by total sampling. Data collection about using computers and smartphones used observation sheets and measuring visual acuity by Snellen charts. The Spearman rank test was employed to examine the relationship between variables. Results: The use of computers and smartphones shows that in the high category as many as 10 (15%) respondents, 24 (37%) respondents in the medium category, and 31 (48%) in the low category. The results of the examination of visual acuity in the normal category were 4 respondents (6%), the nearly normal category were 30 (46%) respondents, and the less moderate category were 31 (48%) respondents. The P value (Sig. 2-tailed) is 0.000 with α 0.05, so 0.000 <0.05, meaning that there was a significant relationship between computer and smartphone use with a decrease in visual acuity. Conclusion: The study shows that there was a relationship between the use of computers and smartphones with a decrease in visual acuity